2020
DOI: 10.1111/een.12998
|View full text |Cite
|
Sign up to set email alerts
|

Differential thermal tolerance across life stages under extreme high temperatures crossed with feeding status in corn leaf aphid

Abstract: 1. Climate change is expected to increase the frequency and duration of extreme heat events, which would pose significant challenges to most ectotherm species, such as insects. 2. In the study, we address the thermal tolerance of corn leaf aphid, Rhopalosiphummaidis (Hemiptera: Aphididae) under brief extreme high‐temperature events (i.e. heat waves) across life stages. Immature instars and adults of R. maidis were exposed to heat events of increasing temperatures (0.5 °C min−1), starting at 22 °C and reaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…S1). These stages also differ in thermal responses and sensitivity, with early life-history stages tending to have lower tolerances (higher sensitivity) to stress than older life stages (Pincebourde and Casas 2015, Qi et al 2019, Chen et al 2021). Therefore, it is essential to understand drivers of thermal tolerances across ontogeny for predicting the persistence of species.…”
Section: Introductionmentioning
confidence: 99%
“…S1). These stages also differ in thermal responses and sensitivity, with early life-history stages tending to have lower tolerances (higher sensitivity) to stress than older life stages (Pincebourde and Casas 2015, Qi et al 2019, Chen et al 2021). Therefore, it is essential to understand drivers of thermal tolerances across ontogeny for predicting the persistence of species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we only tested a single clonal type, but multiple R. padi clones are present in populations [ 72 , 73 ] and can differ substantially in terms of life history characteristics [ 74 ]. Other measures of thermotolerance beyond CT max and knockdown time could be considered given that the aphid life stage when heat exposure occurs can impact thermotolerance [ 75 , 76 , 77 ]. Sublethal life history traits are also influenced by stage-specific exposures to heat stress [ 78 , 79 ], which could shape the interactions between BYDV and R. padi under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The corn leaf aphid, Rhopalosiphum maidis (Fitch), is one of the most economically damaging aphid pests on maize ( Zea mays ) and can transmit several damaging maize viruses, resulting in serious yield losses ( Chen et al., 2019 ; Chen et al., 2020 ), whereas only sporadic reports focus on R. maidis symbionts. Previous studies have tested the symbiont combination of R. maidis and other aphid species collected across Morocco and found that aphid symbiont combinations were mainly host-specific ( Fakhour et al., 2018 ), detected the infection patterns of seven facultative symbionts of R. maidis distributed in 37 geographical populations in China ( Guo et al., 2019 ), and demonstrated that some symbionts may have a direct effect on aphids’ adaptation to different maize management systems ( Csorba et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%